2011
DOI: 10.1179/2042618610y.0000000001
|View full text |Cite
|
Sign up to set email alerts
|

Placebo response to manual therapy: something out of nothing?

Abstract: The mechanisms through which manual therapy inhibits musculoskeletal pain are likely multifaceted and related to the interaction between the intervention, the patient, the practitioner, and the environment. Placebo is traditionally considered an inert intervention; however, the pain research literature suggests that placebo is an active hypoalgesic agent. Placebo response likely plays a role in all interventions for pain and we suggest that the same is true for the treatment effects associated with manual ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
52
1
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(56 citation statements)
references
References 94 publications
0
52
1
3
Order By: Relevance
“…6,21,29 Recently, Bialosky et al 4 suggested that the placebo effect may also be part of the mechanism of manual therapy, and that the failure of a manual therapy intervention to perform better than a placebo does not necessarily indicate a failed intervention, if both outperform the natural history of the condition. The present study was not able to include a nontreatment group by which to compare the natural history of the condition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6,21,29 Recently, Bialosky et al 4 suggested that the placebo effect may also be part of the mechanism of manual therapy, and that the failure of a manual therapy intervention to perform better than a placebo does not necessarily indicate a failed intervention, if both outperform the natural history of the condition. The present study was not able to include a nontreatment group by which to compare the natural history of the condition.…”
Section: Discussionmentioning
confidence: 99%
“…Pretreatment and posttreatment values for thoracic and scapular kinematics and thoracic excursion are listed in TABLES 2 through 4. FIGURE 4 provides graphical representations of the kinematic variables. The patient-reported outcomes for the NPRS, Penn Shoulder Score, and GROC are included in TABLE 5.…”
mentioning
confidence: 99%
“…The mechanical stimulus and resultant neurophysiological effects are modified by nonspecific factors such as expectation of the patient [58,59], equipoise of the practitioner [60,61], placebo effects [62], contextual factors such as the setting and therapeutic alliance between provider and patient [63]. All of these factors can be decisive in treatment outcomes.…”
Section: Moderating For Effectiveness Of Mtmentioning
confidence: 99%
“…However, placebo-related hypoalgesia is considered to be quite specific and localized to the site of treatment and not a remote site, as in the present case. [23][24][25][26] The relevance of these factors to the clinical outcomes in this case were not considered, but may be an area for further research. In this case, it appeared that the pain at Gerdy's tubercle was masquerading as the primary dysfunction resultant to a painless hypomobility at the calcaneocuboid articulation.…”
Section: Discussionmentioning
confidence: 99%